Analysis of real‐world implementation challenges of chipless RFID tag. Issue 9 (23rd April 2019) - Shrestha, Sika; Karmakar, Nemai Chandra
Abstract : Radio frequency identification (RFID) tags are highly sensitive to material contents of the tagged objects, especially with liquids and metals. The presence of an attached object on the tag can be detrimental for tagID detection. In this study, the RF performance of chipless RFID tag placed on different commercial objects for identification purpose is comprehensively analysed. Probable solutions are proposed for observed issues to make the chipless RFID tags readable on various items such as non‐conductive objects, liquid containers and metal items. The misalignment between the reader antenna and the tag is another issue during the commercial implementation of chipless RFID system. A tri‐planar positioning of the tag has been verified as an appropriate solution in this study. The chipless tag has the potential to read stacked pallets and boxes with liquid/solid contents in warehouse scenarios using the proposed solutions.